The Sacred Space of Saint Paul the Apostle, Lyford Cay - Fielding, William J. (International Journal of Bahamian Studies, 2018)
Saint Paul the Apostle, Lyford Cay, is the most westerly Catholic parish church on the island of New Providence, The Bahamas. It was established to meet the spiritual needs of Roman Catholics most removed from the island’s city, Nassau, when a new community was being developed. The paper will demonstrate how the church building blends the “modern” style of architecture of the mid-20th century as well as Church tradition in its Bahamian architectural context.